Pengaruh Digital Marketing Dan Word Of Mouth Terhadap Minat Berkunjung Di Sanggar Budaya Bliran Sina Watublapi - Yohanes Jeksen Tiago; Antonius Philippus Kurniawan; Paulus Juru (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This study aimed to (1) determine the overview of Digital Marketing, Word of Mouth, and Visit Intention, and (2) analyze the significant influence of Digital Marketing and Word of Mouth on Visit Intention. The population of this study consisted of visitors to Sanggar Budaya Bliran Sina Watublapi. The sample included 100 respondents. Data were collected through questionnaires and analyzed using descriptive inferential methods, specifically multiple linear regression analysis. Hypothesis testing was conducted using the F - test and t - test. The descriptive analysis results indicated that the variables Digital Marketing, Word of Mouth, and Visit Intention were categorized as good. The t - test statistical results showed that the Digital Marketing variable had a significant partial effect on the Visit Intention variable. At the same time, the Word of Mouth variable also had a significant partial effect on Visit Intention. The F - test statistical results demonstrated that both independent variables significantly influenced Visit Intention. The determination analysis indicated that the contribution of the Digital Marketing and Word of Mouth variables to tourist Visit Intention at Sanggar Budaya Bliran Sina Watublapi was 43.2 %, while other factors outside the research variables influenced 56.8 %.